The mouse who owned the sun - Derby, Sally; Henstra, Friso (New York : Four Winds Press, 1993)
A little mouse learns that there is much more to the world than he had ever imagined
Primary
Keywords: Mice -- Juvenile fiction; Perspective (Philosophy) -- Juvenile fiction; Sun -- Juvenile fiction